Highly γ-Regioselective 1,2-Addition of α,β-Unsaturated Oxime Ethers with Allylzinc Bromides: A Straightforward Approach for the Synthesis of Homoallylic Amines - Yang, Bo; Zhang, Songlin (Synthesis, 2019)
A highly regioselective reaction between allylzinc bromide reagents and α,β-unsaturated oxime ethers for the one-step synthesis of the homoallylic amines is reported. This process is a regioselective 1,2-addition reaction providing a new γ-position with carbon–carbon bond formation. Furthermore, the reaction substrates are widely applicable and can be produced in a high yield.
Keywords: regioselectivity; homoallylic amine; α,β-unsaturated oxime ether; organozinc reagent; 1,2-addition